Pengaruh Motivasi dan Komunikasi Interpersonal Kepala Sekolah Terhadap Kinerja Guru - Ardiansyah, Rezza; Wulandari, Catur; Lestari, Neta Dian (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to analyze the impact of motivation and interpersonal communication from school principals on teacher performance at SMA Negeri 6 Prabumulih. The research employs a quantitative approach with a survey design, involving a number of teachers as respondents. The results indicate a significant positive relationship between the motivation provided by the school principal and effective interpersonal communication in enhancing teacher performance. Principals who foster open communication and support can boost teachers’ work morale, thereby contributing to the improvement of the quality of education in the school. These findings underscore the crucial role of school principals in creating a conducive work environment, where effective communication and appropriate motivation can drive teachers to achieve optimal performance. This study is expected to provide insights for developing more effective leadership strategies within the educational context.